Bureaucratic Reform Enhancing Responsiveness of Government Institutions - Futum Hubaib; Akbar Aswin (Indonesian Journal of Accounting and Financial Technology, 2025)
This study examines how bureaucratic reform enhances the responsiveness of government institutions in delivering efficient and adaptive public services. Using a descriptive qualitative approach and a single case study at the Samarinda City Investment and One-Stop Integrated Services Office (DPMPTSP), data were collected through observations, in-depth interviews with ten key informants, and policy document analysis. Findings reveal that organizational restructuring, process simplification, digital service innovation, and a strengthened performance-based work culture significantly improve institutional responsiveness and citizen satisfaction. Nevertheless, challenges remain in sustaining behavioral changes among personnel and integrating digital systems across service units. Overall, the study concludes that bureaucratic reform not only improves administrative efficiency but also fosters adaptive, citizen-centered governance, contributing both theoretically and practically to the advancement of good governance at the local level.